Water-soluble polysaccharides from Grifola Frondosa fruiting bodies protect against immunosuppression in cyclophosphamide-induced mice via JAK2/STAT3/SOCS signal transduction pathways. Issue 8 (29th July 2019) - Meng, Meng; Guo, Mingzhu; Feng, Chengcheng; Wang, Ruhua; Cheng, Dai; Wang, Chunling
Abstract : Grifola Frondosa, the king of mushrooms, is one of the most valued traditional medicines and has been used as a health food for a long time in China, Japan, and other Asian countries. Abstract : Grifola Frondosa, the king of mushrooms, is one of the most valued traditional medicines and has been used as a health food for a long time in China, Japan, and other Asian countries. The present study was designed to evaluate the immune-modulating effects of water-soluble polysaccharides from the Grifola Frondosa fruiting body (GFP) by using mouse peritoneal macrophage and cytoxan (CTX) induced immunosuppression models. Compared with CTX-induced immunosuppressive mice, the spleen and thymus indexes in mice with GFP orally administrated were significantly increased, body weight loss was alleviated, and the natural killer (NK) cytotoxicity and the proliferative activities of lymphocytes were elevated. Furthermore, levels of interleukin-2 (IL-2), interferon-6 (IL-6) and tumor necrosis factor-α (TNF-α) were notably reduced by CTX, while GFP abolished these effects. GFP also effectively increased total antioxidant capacity and superoxidase dismutase, catalase and glutathione peroxidase activities, and inhibited an increase in the malondialdehyde level. Histopathological analysis of spleens revealed the protective effect of GFP against CTX-induced immunosuppression. Western blotting results showed that GFP possessed immunomodulatory activity by up-regulating transcription factors (p-JAK2/JAK2, p-STAT3/STAT3 and SOCS3) in JAK2/STAT3/SOCS signaling pathways. This study suggested that GFP may provide an alternative strategy for lessening chemotherapy-induced immunosuppression.